Monetary and Exchange Rate Policies of the Euro Area. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The economic conditions in the euro area have brightened. Executive Directors commended the policy stance of the European Central Bank. They noted that the exchange rate developments of the euro failed to strengthen the euro area economy, and stressed the need for fiscal discipline, structural reforms, and wage moderation at the national level to maintain price stability in the medium term. They emphasized the need for deeper integration of European Union financial markets, development of risk capital, and improvement of the quality and sustainability of public finances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet